BIOSYNTHESIS OF CHLORAMPHENICOL IV. : Incorporation of Carbon(14)-Labeled Precursors - Gottlieb, David (1962)
Gottlieb, David (University of Illinois, Urbana), H. E. Carter, P. W. Robbins, and R. W. Burg. Biosynthesis of chloramphenicol. IV. Incorporation of carbon(14)-labeled precursors. J. Bacteriol. 84:888–895. 1962.—Metabolism of dl-phenylalanine stimulated antibiotic synthesis by Streptomyces venezuelae, and resulted in the fixation of carbons 1 and 2 into the carbonyl group of chloramphenicol. It probably occurs by the oxidation of these carbons to carbon dioxide, followed by incorporation. Carbon 3 and the adjacent ring carbon were found in the dichloromethyl and the carbonyl carbons, respectively, of the dichloroacetyl portion of the molecule. The phenyl group of the amino acid is not transferred to the ring in chloramphenicol. Another stimulatory amino acid, dl-norleucine, contributed carbon 2 only as the carbonyl carbon. dl-Leucine is metabolized so that two adjacent carbons appear as the carbons in the dichloroacetyl moiety of the antibiotic. From acetic acid, carbon 1 is found only in the carbonyl group of chloramphenicol; carbon 2 of the acid is more generally distributed among the ring and side chain of the p-nitrophenylserinol part of the antibiotic, but is in greatest concentration in the dichloroacetyl fraction. Formic acid and carbon dioxide also are transformed only to the carbonyl group. Glycerol, the main source of metabolized carbon in the medium, has a general role and contributes to all parts of the molecule. In addition, it has a specific role in supplying an intact three-carbon fragment which enters into the molecule of chloramphenicol as a unit.